Female voices and bodies in “Le Printemps”: an invitation, via annotated English translations, to bring Agrippa d’Aubigné’s love poetry into comparative literature courses - Worth-Stylianou, V (OpenEdition Journals, 2025)
Le Printemps deserves to feature in comparative literature courses on love poetry. To encourage my colleagues to take up this challenge, I provide an annotated English translation, for university students, of four poems from the collection. The two shorter and two longer poems all share a focus either on the female voice, or on a female body without a voice. I ask whether, when d’Aubigné lends his voice to a female character – whether his wife or an Ovidian heroine –, he is really giving them agency, or rather strengthening his own control through their voices. In addition, these poems showcase the wide range of styles with which d’Aubigné experiments in Le Printemps, and I argue that to appreciate them it is also crucial to recognise the intertextual dialogues he sets up with classical and contemporary poets.